Treatment of Cutaneous Neurofibromas in Patients with Neurofibromatosis Type 1 - Bartosz Wozniak; Torsten Bove; Tomasz Zawada; Jacek Calik (Karger Publishers, 2023)
Neurofibromatosis type 1 is a genetic disorder impacting approximately 2.5 million people worldwide, often leading to development of numerous benign yet disfiguring cutaneous neurofibromas (cNF). Removal of cNF is limited to excision or laser ablation with common post-operation complications and scarring. The current case explores a new approach to removal or reduction of cNF by a minimally invasive and pain-reduced treatment modality. A 40-year-old female patient with numerous cNF across her body underwent a single treatment using a 20 MHz dermatologically focused ultrasound device on seven selected cNF on the upper back. Each cNF was treated in a single session of 20-60 s without anesthesia due to manageable pain. Only one minimal adverse reaction in the form of dyspigmentation in a single treated tumor was noted from treatment or during the healing of a thin scab that formed on each cNF a few days after treatment. At the 12-month follow-up, four out of seven treated cNF showed full remission, two showed partial or significant reduction in tumor volume, while two did not respond to treatment. The reason for the variability is not fully understood, but speculations include difference in tissue content, e.g., due to tumor age. The method is concluded to be a promising candidate for a new safe and minimally invasive treatment that can potentially be used for single-session removal/reduction of a large number of cNF. Further research should focus on refining treatment parameters and strategies to enhance response predictability.